Analisis Parameter Genetik dan Komponen Ragam Untuk Peningkatan Mutu Genetik Domba Jantan Lokal dan Kambing Kacang Tahun 2023 - Joharsah, Joharsah; Kartono, Kartono; Syahputra, Muahmmad Ary; RS, Muttaqinullah; Arwinsyah, Arwinsyah; Hadirin, Hadirin; Zendrato, Desti Prestasi (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2023)
This article aims to identify the genetic variability controlling growth and production traits in local male sheep and Kacang goats, as well as estimate genetic parameters and variance components to enhance their genetic quality. Conducted at the Loka Pengabdian Kambing Potong, Sei Putih, the research employed a quantitative descriptive approach, collecting data on birth weight, weaning weight at three months, and pre-weaning growth rate. The analysis utilized statistical models to estimate heritability, repeatability, and breeding values, providing a comprehensive understanding of the genetic potential of these animals. The results revealed significant genetic diversity that could be leveraged for selective breeding programs to improve productivity and competitiveness of local livestock. The study underscores the importance of systematic breeding programs not only for increased production but also for the conservation of valuable genetic resources, contributing to food security and rural development in Indonesia.